School climate and associated factors: A structural equation modeling - Cuadra-Martínez, David [UNESP]; Pérez-Zapata, Daniel; Sandoval-Díaz, José; Rubio-González, Juan (Sistema de Bibliotecas PUCP, 2022)
The aim of this work was to propose a latent equation model that structures the relationship between academic engagement, schadenfreude and prosocial behavior on the school climate. We used a cross-sectional design and 437 secondary students from Chile were recruited. School Climate Scale, Engagement UWES-S 9, School Prosocial Behavior Inventory and Schadenfreude scale were administered. Factor analysis, reliability test, correlation analysis and structural equation modeling were performed to analysis data. After fitting two models for our data and contrasting them with theoretical literature, we found that school climate was affected directly by school engagement and prosocial behavior. Academic engagement positive affects, direct and indirectly, the school climate. An increase in academic engagement also lowers the levels of schadenfreude and causes an increase in the levels of prosocial behaviour. Results are discussed and possible implications are highlighted, considering limitations and suggestions that might guide practical interventions on school climate.
Clima escolar y factores asociados: modelo predictivo de ecuaciones estructurales
Climat scolaire et facteurs associés: modèle prédictif d’équations structurelles
Keywords: prosocial behavior; schadenfreude; school climate; school engagement; structural equation modeling